2020
DOI: 10.1177/2309499020929786
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative denosumab treatment with curettage may be a risk factor for recurrence of giant cell tumor of bone

Abstract: Purpose: Giant cell tumor of bone (GCTB) is a local aggressive bone tumor, histologically classified as intermediate malignancy. Recently, the RANKL inhibitor, denosumab, was developed as a novel and effective treatment option for GCTB. Since the risk of preoperative use of denosumab with curettage had been previously reported, this study aimed to investigate the relationship between recurrences and clinicopathological features associated with adjuvant denosumab treatment in GCTB. Methods: A total of 87 GCTB c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…Denosumab, a RANK ligand inhibitor, is frequently used now in the treatment of GCTB, especially for unresectable tumors. 27 , 28 Favorable outcome following its use have been reported 46 , 47 but some recent studies reported otherwise. 48 , 49 By multivariate analysis, our study shows that denosumab therapy increases the risk for local recurrence as a significant trend level ( P = 0.053).…”
Section: Discussionmentioning
confidence: 99%
“…Denosumab, a RANK ligand inhibitor, is frequently used now in the treatment of GCTB, especially for unresectable tumors. 27 , 28 Favorable outcome following its use have been reported 46 , 47 but some recent studies reported otherwise. 48 , 49 By multivariate analysis, our study shows that denosumab therapy increases the risk for local recurrence as a significant trend level ( P = 0.053).…”
Section: Discussionmentioning
confidence: 99%
“…For various clinicopathological factors like age, gender or localization of GCTB but even for joint affection or the presence of metastases no significant association with local recurrence was found in the recent study. Sano et al [14] did not find any association between various clinicopathological factors such as age, gender, surgical site, Campanacci grade or pathological fracture and local recurrence either in a study of 87 patients with GCTB.…”
Section: Discussionmentioning
confidence: 88%
“…There is a debate if denosumab administered before curettage may increase the likelihood of local recurrence [13] . Sano et al [14] demonstrated in a study of 87 patients with GCTB that the use of denosumab prior to curettage possibly increase the risk of local recurrence. Tsukamoto et al [13] conclude in a systematic review that neoadjuvant denosumab application may increase the likelihood of local recurrence after intralesional curettage of GCTB.…”
Section: Introductionmentioning
confidence: 99%
“…Totally, we only included a total of 11 studies in our meta-analysis. 4,10,16,19,30,31,[34][35][36][37] We summarize the paper selection in Figure 1. We describe the baseline characteristics of our studies in Table 1.…”
Section: Eligible Studiesmentioning
confidence: 99%